Programma: 27 juni: Time Fuckers; 1 juli: Music, war, radio; 8 juli: Consolidated, I.Q.; 9 juli: Robert Gordon + Chris Spedding (1993)
Programma: 27 juni: Time Fuckers; 1 juli: Music, war, radio; 8 juli: Consolidated, I.Q.; 9 juli: Robert Gordon + Chris Spedding.